ChemInform Abstract: Bi—Zn Bond Formation in Liquid Ammonia Solution: [Bi—Zn—Bi]4‐, a Linear Polyanion that is Iso(valence)‐electronic to CO2. Issue 48 (2nd December 2014) - Benda, Christian B.; Koechner, Tobias; Schaeper, Raphaela; Schulz, Stephan; Faessler, Thomas F.
Abstract (III) crystallizes as black block‐shaped crystals in the monoclinic space group C2/c with Z = 4 (single crystal XRD) and contains isolated, linear heteroatomic [Bi—Zn—Bi]4‐ anions.